Pesan Ukhuwah Islamiyah Pada Film Cahaya Cinta Pesantren Karya Ira Madan: Analisis Semiotika Roland Barthes - Fahira, Jirza Raisa; Faridah (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Ukhuwah Islamiyah is a unique concept in Islamic culture that establishes brotherhood between Muslims based on Islamic beliefs and teachings. It is hoped that this brotherhood can become a basis for unity, solidarity, mutual cooperation, strengthening and respecting differences in everyday life. As social creatures we need to blend in with the surrounding environment, in this case introduction or ta'aruf is the main basis for getting to know and understand each other. Namely how we feel about the burdens, difficulties and even happiness that we can carry together so that we can create a society with strong Islamic brotherhood. Rasulullah SAW likened a Muslim and other Muslims to one body, if his brother feels pain then he also feels the same thing. Like in the film Cahaya Cinta Pesantren by Ira Madan, we can find many values of Islamic brotherhood in it. In this research, a qualitative method was used using Roland Bathers' semiotic method. There are three aspects that show that the film "Cahaya Cinta Pesantren" not only has a general meaning but also has denotation, connotation and myth.